Sustainability of biodegradable plastics: New problem or solution to solve the global plastic pollution? - Taofeeq, D. Moshood; Gusman, Nawanir; Fatimah, Mahmud; Fazeeda, Mohamad; Mohd Hanafiah, Ahmad; Airin, Abdul Ghani (Elsevier B.V., 2022)
Plastic usage is increasing the number of pollutants in the environment. Plastic particles and other plastic-based pollutants are found in our environment and food chain, posing a threat to human health. From this perspective, the biodegradable plastics material focuses on creating a more sustainable and greener world with a smaller environmental imprint. This assessment should consider the entire life cycle assessment of the objectives and priorities for producing a wide range of biodegradable plastics. Biodegradable plastics can also have properties similar to traditional plastics while also delivering additional benefits due to their minimised impact on the environment in terms of carbon dioxide, as long as appropriate waste management includes such as composting, are contained. The demand for cost-effective, eco-friendly materials increases to reduce waste management and pollution issues. This study seeks to comprehensively understand biodegradable plastics production and applications research, product prospects, sustainability, sourcing and ecological imprint. Academic and industry interest in biodegradable plastics for sustainability has exploded in recent years. Researchers used the triple bottom line to analyse the sustainability of biodegradable plastics (economic profit, social responsibility, and environmental protection). The research also discusses the variables that influence the adoption of biodegradable plastics and a sustainable framework for improving biodegradable plastics' long-term viability. This study provides a thorough yet simple theoretical design of biodegradable plastics. The research findings and future research endeavours provide a new avenue for further research and contribution to the area.